“Diseño de un sistema de gestión de calidad basado en la normativa ISO: 9001:2015 para mejorar los procesos en la empresa Indupalets” - Castro Mazón, Lucy Gabriela (2020)
This work is basing on the design of a Quality Management System based on the ISO 9001:2015 standard in the company Indupalets Ltd., which allows us to improve the processes of in the firm, with the benefit of providing a quality service for our customers. A diagnosis of the different causes found through a checklist based on the criteria of ISO 9001:2015 to reduce these problems. A quality manual was developed, which clearly defines its policy, objectives, as well as its structure, processes, and responsibilities of the SGS; and as a compliment, any information was collected for carrying out the procedures, records, and formats; which are certain criteria that govern the norm. The sequence and the interrelationship of the processes were established to get a better organization in the company that helps the performance of the company's activities, aimed at the improvement of procedures that allow greater satisfaction of our customers and bring to the organization to continual improvement. This study guarantees an alternative of compliance with the requirements of the customers and a better organization of the company.